An alternative apparatus for measuring electrical resistance - Castillo, Celso P. (Animo Repository, 1995)
This study aimed to develop, construct and test an alternative apparatus for the commercial ohmmeters using low-cost and locally available materials. In the course of the investigation, an improvised instrument was constructed, making use of a circuit design that utilizes the principle of the Wheatstone bridge circuit. To test the apparatus, laboratory activities that involved measurement of resistance were performed. An analog ohmmeter and a digital ohmmeter were used as standard instruments. The data gathered were subjected to a t-test. The study came up with the following results and conclusions: 1. The design of the apparatus was simple. Its main circuit consisted only of 8 carbon resistors and a variable resistor. 2. The cost of constructing the device was only P164.20 (as of September 1995). This is much less than the price of commercial multi testers which runs from about P400.00 to more than P1,000.00. 3. A galvanoscope and a zero-center type of galvanometer must both be used as essential parts of the apparatus. The use of the galvanometer increases its sensitivity. 4. The substitute device could measure a resistance range of 0.5 to 10,000 ohms at a precision comparable to that of the commercial ohmmeters. 5. In general, the performance of the apparatus did not differ significantly from those of the analog and digital ohmmeters of the .05 level of significance. It compares better with the digital ohmmeter at the .01 level. Based on the findings and conclusions, the following were recommended: 1. A more sensitive design of a galvanoscope be constructed so as to relieve the substitute apparatus of the need for a galvanometer. 2. Further research be made concerning the possibility of designing a sensitive current detector circuit that makes use of light-emitting diodes and transistors. This circuit may be integrated into the improvised apparatus. 3. The circuit design of the apparatus be improved so that it will be able to perform other functions beside measuring electrical resistance.